Analysis of Hadith on Three Factors of Happiness: Perspective of Housing Development - U Saifuddin ASM; Ulvah Nur'aeni; Aep Kusnawan; Muhammad Zuldin; Yusuf Zainal Abidin (AN NUR: Jurnal Studi Islam, 2025)
This study aims to examine the relevance of the Prophet's hadith from the narration of Ahmad (164H-241H) number 14830 regarding the aspects of a person's happiness, which consist of righteous neighbors, comfortable transportation, and a spacious house in the context of housing development in the modern era. The study was conducted using a qualitative approach based on hadith literature analysis and sustainable development theory. The results of the study show that this hadith has a value that is very relevant to contemporary human needs. First, the concept of spacious house is understood as a decent, healthy dwelling that supports family welfare. Second, a righteous neighbor emphasizes the importance of social harmony in the housing environment, which is a major factor in creating peace of mind. Third, comfortable vehicle can be interpreted as a means of transportation that is safe, efficient, and environmentally friendly, which supports the daily activities of housing residents. This study concludes that the hadith provides an ethical and philosophical framework that is in line with the concept of modern development, particularly in creating a holistic residential environment: paying attention to physical aspects, social aspects, and mobility. Theoretically, this study enriches the study of the integration of hadith with sustainable development. Practically, the results of this study can be used as a reference for the government, developers, and the community in designing and building residential environments that are not only economically oriented but also focused on physical and spiritual well-being.